CRISPR/Cas9-Engineered Large Fragment Deletion Mutations in Arabidopsis CEP Peptide–Encoding Genes Reveal Their Role in Primary and Lateral Root Formation - Huang, Aixia; Cui, Tingting; Zhang, Yan; Ren, Xufang; Wang, Mengfang; Jia, Lingyu; Zhang, Yonghong; Wang, Guodong (Plant and cell physiology, 2023)
Abstract C-TERMINALLY ENCODED PEPTIDEs (CEPs) are post-translationally modified peptides that play essential roles in root and shoot development, nitrogen absorption, nodule formation and stress resilience. However, it has proven challenging to determine biological activities of CEPs because of difficulties in obtaining loss-of-function mutants for these small genes. To overcome this challenge, we thus assembled a collection of easily detectable large fragment deletion mutants of Arabidopsis CEP genes through the clustered regularly interspaced short palindromic repeat/CRISPR-associated protein 9–engineered genome editing. This collection was then evaluated for the usability by functionally analyzing the Arabidopsis growth and development with a focus on the root. Most cep mutants displayed developmental defects in primary and lateral roots showing an increased primary root length and an enhanced lateral root number, demonstrating that the genetic resource provides a useful tool for further investigations into the roles of CEPs.